1995
DOI: 10.1063/1.469562
|View full text |Cite
|
Sign up to set email alerts
|

Ni2 revisited: Reassignment of the ground electronic state

Abstract: Resonant two-photon ionization spectroscopy was used to study jet-cooled Ni2 produced by pulsed laser ablation of a nickel target in the throat of a supersonic nozzle using argon as the carrier gas. Spectral regions previously investigated using helium as the carrier gas were reinvestigated, and the improved cooling achieved was found to suppress transitions arising from an Ω=4 state that had been thought to be the ground state. Seven new vibronic progressions were assigned, with spectroscopic constants determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
57
2
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(85 citation statements)
references
References 27 publications
15
57
2
1
Order By: Relevance
“…The calculated data of 2.221 (1.125), 2.213 (1.215) and 2.111 (1.563) Å (eV) agree fairly well with experiments [29,[33][34][35][36][37], respectively. We note that though the Ni-Cu bond length is slightly smaller than that of the Cu-Cu, the average binding energy of the NiCu dimer is clearly larger than that of the Cu 2 dimer, thus the Ni atom prefers a high-coordination site so as to enhance the total binding energy.…”
Section: Geometric Structures Of Cu N Clusters (N = 2-13)supporting
confidence: 78%
“…The calculated data of 2.221 (1.125), 2.213 (1.215) and 2.111 (1.563) Å (eV) agree fairly well with experiments [29,[33][34][35][36][37], respectively. We note that though the Ni-Cu bond length is slightly smaller than that of the Cu-Cu, the average binding energy of the NiCu dimer is clearly larger than that of the Cu 2 dimer, thus the Ni atom prefers a high-coordination site so as to enhance the total binding energy.…”
Section: Geometric Structures Of Cu N Clusters (N = 2-13)supporting
confidence: 78%
“…The bond lengths of M 2 are summarized in Table I. [33][34][35][36] The calculations agree fairly well with the experiments with a difference of only 0.04 Å at most. One exception was Mn 2 , where the present calculation predicted the spin multiplicity of 11, while the singlet ground state is reported for matrix-isolated Mn 2 by the electron-spin-resonance experiment.…”
Section: Computational Proceduressupporting
confidence: 51%
“…The bond energy for Ni 2 comes from Pinegar et al 22 and not the earlier value that was determined by Morse et al 23 and reported by Lombardi and Davis. 20 The equilibrium bond lengths (r e ) for Cr 2 , Cu 2 , Mo 2 , and V 2 also come from Lombardi and Davis.…”
Section: Databasesmentioning
confidence: 95%